2019
DOI: 10.1021/acsaelm.9b00701
|View full text |Cite
|
Sign up to set email alerts
|

Toward Fully Printed Memristive Elements: a-TiO2 Electronic Synapse from Functionalized Nanoparticle Ink

Abstract: Electronic devices that emulate bio-functionalities, such as synaptic plasticity, present a promising route to versatile and energy-efficient neuromorphic computing systems. As the demand for rapid-prototyping and environmentally-friendly fabrication of such devices rises, there are significant incentives toward finding solutions for low cost materials and flexible

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 69 publications
0
17
1
Order By: Relevance
“…Inkjet printers are used for automated drop casting and typically operate with a picoliter droplet volume and provide droplet deposition with 10–20 μm spatial resolution. The thickness of the film may be variable and usually exceeds 100 nm (Duraisamy et al, 2012 ), although a lower value of 80 nm has been reported recently (Salonikidou et al, 2019 ).…”
Section: Synthesis and Fabricationmentioning
confidence: 99%
“…Inkjet printers are used for automated drop casting and typically operate with a picoliter droplet volume and provide droplet deposition with 10–20 μm spatial resolution. The thickness of the film may be variable and usually exceeds 100 nm (Duraisamy et al, 2012 ), although a lower value of 80 nm has been reported recently (Salonikidou et al, 2019 ).…”
Section: Synthesis and Fabricationmentioning
confidence: 99%
“…Memristor is consisted of bottom and top metallic electrodes with sandwiched switching layer. In the literature, memristor size varies from nm to micrometer depending on the technology used in the development of memristor [55]. Commonly, the printed memristor are comparatively of large size i.e., in micrometer whereas, the solid state memristors are in nanometer size.…”
Section: Memristor Fabrication Techniquesmentioning
confidence: 99%
“…The dominance of EHD printing methods for fabricating memristive structures is attributed to the high patterning resolution which can be achieved with this technique and which can extent below 100 nm [26]. Nevertheless, a number of fully printed memristive systems using the standard ink-jet technique [27][28][29][30][31] and aerosol jet printing [32,33] have been reported.…”
Section: State-of-the-artmentioning
confidence: 99%